Founder genetic variants of ABCC4 and ABCC11 in the Japanese population are not associated with the development of subacute myelo‐optico‐neuropathy (SMON). Issue 1 (24th December 2021) - Matsumoto, Hideki; Sasai, Hideo; Kawamoto, Norio; Katsuyama, Masato; Minamiyama, Makoto; Kuru, Satoshi; Fukao, Toshiyuki; Ohnishi, Hidenori
Abstract: Background: Subacute myelo‐optico‐neuropathy (SMON) is a severe neurological disorder associated with clioquinol administration, which frequently occurred in Japan during the 1950s and 1960s. The unique genetic background of the Japanese population is considered to be strongly involved in the development of this neurological disease. Recently, genetic variants of ABCC4 (OMIM: 605250) and ABCC11 (OMIM: 607040), which are particularly common in the Japanese population, were suggested as possible genetic susceptibility factors for the development of SMON. Methods: We analyzed 125 Japanese SMON patients who provided consent for this study. Patient DNA was collected from peripheral blood, and genetic analysis was performed for ABCC4 rs3765534 (c.2268G>A, p.Glu857Lys) and ABCC11 rs17822931 (c.538G>A, p.Gly180Arg) polymorphisms using the Sanger sequencing method and/or TaqMan PCR method. The frequency distribution of each polymorphism was compared with that in healthy Japanese people recorded in two genomic databases (Human Genomic Variation Database and Integrative Japanese Genome Variation Database), and each genotype was compared with the clinical features of patients. Results: The frequencies of ABCC4 rs3765334 and ABCC11 rs17822931 polymorphisms in SMON patients and healthy Japanese people were not significantly different in the multifaceted analysis. Conclusion: We conclude that the ABCC4 rs3765334 and ABCC11 rs17822931 polymorphisms are not associated with the development of SMON. Abstract : Frequency distribution of the ABCC4 rs3765334 and ABCC11 rs17822931 polymorphisms in subacute myelo‐optico‐neuropathy patients and healthy Japanese people in genetic databases (Human Genomic Variation Database and Integrative Japanese Genome Variation Database).